PENGARUH KUALITAS SUMBER DAYA MANUSIA DALAM PENGELOLAAN KEUANGAN TERHADAP KUALITAS PERTANGGUNGJAWABAN KEUANGAN PNBP DALAM UPAYA MENINGKATKAN KINERJA INSTANSI PADA UNIVERSITAS SYIAH KUALA - Arsyiati Arsyiati; Darwanis Darwanis; Muslim A Djalil (Jurnal Telaah dan Riset Akuntansi, 2008)
This research is done at Syiah Kuala University with aim to know how big influence of human resource quality in finance management to finance responsibility quality at Unsyiah, and to know there is or no influence of human resource quality  in finance management and quality of finance responsibility to institution performance at Unsyiah with parsial or simultan.        Responden in this research is assistant of PUMK and finance organizer at Syiah Kuala University which responsible in finance management.  This research type have the character of korelasional with 35 people samples of populations 53 people who is taken at random proporsional. Technics of data analysis the used is path analysis.       Result of this research indicate that the human resource quality in finance management to finance responsibility quality don't have influence which significan, while influence of human resource quality in finance management and finance responsibility quality to institution performance by simultan have influence which  significan, but by parsial influence of each independent variable to dependen variable have different significan.  Keyword : Human resource quality, finance responsibility quality, and institution performance.